Cut and Paste: The Mexican Axolotl, Experimental Practices and the Long History of Regeneration Research in Amphibians, 1864-Present - Reiß, Christian (Frontiers in Cell and Developmental Biology, 2022)
The Mexican axolotl (Ambystoma mexicanum) is one of the most important models in contemporary regeneration research and regenerative medicine. This is the result of the long history of the species as an experimental and laboratory bred animal. One of many research questions investigated in the axolotl is regeneration. The species’ astonishing ability to regenerate tissues and entire body parts already became apparent shortly after the first 34 living axolotls had been brought from Mexico to Europe in 1864. In the context of their unclear status as larvae or adults and the mysterious transformation of some animals into an adult form, the Paris zoologist Auguste Duméril cut off the gills of several individuals in an attempt to artificially induce the metamorphosis. This produced the first reports on the animals’ regenerative powers and led to sporadic but continuous investigations. But it remained just one of the many phenomena studied in axolotls. Only at the beginning of the 20th century, regeneration became more a more prominent aspect in the experimental investigations of axolotls.. In experimental embryology, regeneration in axolotls was used in three different ways: it was studied as a phenomenon in its own right: more importantly, it served as a macroscopic model for normal development and, together with other techniques like grafting, became a technical object in the experimental systems of embryologists. In my paper, I will look into how the axolotl became an experimental animal in regeneration research, the role of practices and infrastructures in this process and the ways in which regeneration in the axolotl oscillated between epistemic thing and technical object.